Role of Family Planning in Women With Multiple Sclerosis in Switzerland: Results of the Women With Multiple Sclerosis Patient Survey - Kamm, Christian P.; Muehl, Sarah; Mircsof, Dennis; Müller, Stefanie; Czaplinski, Adam; Achtnichts, Lutz; Stellmes, Petra; Di Virgilio, Gabrielle (Frontiers in Neurology, 2018)
Background: Women of child bearing age with multiple sclerosis (MS) must carefully consider treatments when planning a family, since disease modifying drugs (DMDs) are contraindicated during pregnancy. Objectives: This questionnaire-based study aimed to improve understanding of the effect of family planning on treatment decisions in female, Swiss MS patients. Methods: Female patients with MS (aged 18–55 years) participated in the 26-question survey between September 2014 and August 2015. Information captured included patient background, family planning status, treatment course and previous pregnancies. Results: In total, 271 questionnaires distributed from 15 MS centres were returned for analysis. Of these, 250 (92.3%) participants received DMD therapy and 106 (39.1%) wanted children or were pregnant. Significantly more patients with a short-term plan to conceive within 2 years were treated with injectables (19/54) compared with those without a plan to conceive (19/108; p=0.013). A proportionally greater number of women not planning to conceive took oral (34/108) or infusion therapies (41/108) compared with those with a short- (13/54 and 16/54 respectively) or medium-term (after two years or more; infusion therapy only, 14/44) plan to conceive. Conclusion: The study highlights that pregnancy remains an important yet unresolved concern in the treatment of MS patients. Nearly all women received DMD treatment, and type of DMD treatment was influenced by family planning, with significantly more women with a short-term plan to conceive using injectables.